Uganda NAPA meeting - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The CGIAR Research Program on Climate Change, Agriculture and Food Security, East Africa in partnership with the Ministry of Water and Environment, Climate Change Unit in Uganda, brought together players in the agricultural and environment sectors to discuss ways of taking forward the implementation of the agricultural priority actions in the National Adaptation Programme of Action (NAPA) of Uganda. Photos S.Kilungu (CCAFS)